Single crystal high nickel positive electrode material and its preparation method and use

The Ti/Co co-coating method addresses the issue of high residual alkali in high nickel cathode materials, enhancing cycle stability and rate performance, and improving battery efficiency and cost-effectiveness.

JP7656056B2Active Publication Date: 2025-04-02SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023549940
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-04-28
Filing Date
2021-11-12
Publication Date
2025-04-02
Estimated Expiration
2041-11-12

AI Technical Summary

Technical Problem

High residual alkali content in high nickel ternary nickel cobalt lithium manganate and nickel cobalt lithium aluminum cathode materials leads to water absorption, coating difficulties, increased electrolyte activity, and reduced battery cycle performance.

Method used

The use of a Ti/Co co-coating method during the preparation of single crystal high nickel cathode materials significantly reduces residual alkali content, while maintaining high capacity and rate performance through a specific method involving precursor mixing, sintering, and secondary coating.

Benefits of technology

The Ti/Co co-coating method effectively reduces alkali content, enhancing the cycle stability and rate performance of single crystal high nickel cathode materials, thereby improving battery performance and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656056000003
    Figure 0007656056000003
  • Figure 0007656056000004
    Figure 0007656056000004
  • Figure 0007656056000001
    Figure 0007656056000001
Patent Text Reader

Abstract

The present disclosure provides a monocrystalline high-nickel positive electrode material and a preparation method and use thereof, the preparation method including: step (1) of mixing a precursor, a lithium source and a nano-oxide, and performing a primary sintering process under an oxygen-containing atmosphere to obtain a primary sintered material; and step (2) of mixing the primary sintered material obtained in step (1) with a titanium source and a cobalt source, and performing a secondary sintering process under an oxygen-containing atmosphere to obtain the monocrystalline high-nickel positive electrode material. The present disclosure employs a Ti / Co co-coating method to greatly reduce the residual alkali content of the prepared monocrystalline high-nickel positive electrode material, while maintaining a high level of capacity and rate performance, thereby reducing the process flow and saving costs.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to the field of lithium ion batteries, including, for example, to single crystal high nickel positive electrode materials and methods for their preparation and use. [Background technology]

[0002] When synthesizing high-nickel ternary nickel cobalt manganese oxide (NCM) cathode material or nickel cobalt aluminum oxide (NCA) cathode material, the material surface has a high residual alkali content and is easy to absorb water. On the one hand, it makes the subsequent coating of the cathode material difficult, and at the same time, it puts higher requirements on the electrolyte in terms of alkali resistance. High alkalinity will cause the battery to swell during the cycle process, which will further affect the cycle performance of the battery. On the other hand, in the charged state, Ni will remain on the surface of the cathode material particles. 4+ exists, and Ni 4+ Since the activity of is high and side reactions with the electrolyte tend to occur, the impedance of the battery increases, resulting in irreversible capacity loss.

[0003] The most common solution to the above problem at present is to improve the cycle performance and rate performance of the material by washing the positive electrode material with water, coating, and complex structure design, but the improvement effect is not desirable. Summary of the Invention [Problem to be solved by the invention]

[0004] The present disclosure provides a single crystal high-nickel positive electrode material and its preparation method and use. By adopting a Ti / Co co-coating method, the residual alkali content of the prepared single crystal high-nickel positive electrode material is greatly reduced while maintaining a high level of capacity and rate performance, thereby reducing the process flow and saving costs. [Means for solving the problem]

[0005] The present disclosure provides in one embodiment a method for preparing a single crystal high nickel positive electrode material, the method comprising: (1) mixing a precursor, a lithium source and a nano-oxide, and obtaining a primary sintered material by a primary sintering process under an oxygen-containing atmosphere; and step (2) mixing the primary sintered material obtained in step (1) with a titanium source and a cobalt source, and subjecting the primary sintered material to a secondary sintering process in an oxygen-containing atmosphere to obtain the single crystal high-nickel positive electrode material.

[0006] The present disclosure employs the doping of nano-oxide with precursor and lithium source to reduce the mixing of lithium nickel, stabilize the crystal structure, improve the conductivity of the electrode material, and further improve the safety and long-term cycle stability of the battery. The present disclosure employs the Ti / Co co-coating method to significantly reduce the residual alkali content of the prepared single crystal high nickel positive electrode material while maintaining high capacity and rate performance, thereby reducing the process flow and reducing costs.

[0007] In one embodiment, the precursor in step (1) is Ni x Co y Mn z (OH) 2 Includes 、 x≧0.8, such as 0.8, 0.82, 0.85 or 0.88; 0.2≧y≧0, such as 0, 0.05, 0.1, 0.15 or 0.2; 0.2≧z≧0, such as 0, 0.05, 0.1, 0.15 or 0.2; and x+y+z=1.

[0008] In one embodiment, the lithium source in step (1) comprises lithium hydroxide and / or lithium carbonate.

[0009] In one embodiment, the nano-oxide in step (1) comprises any one or a combination of at least two of zirconium oxide, titanium oxide, tungsten oxide, molybdenum oxide, alumina, or yttrium oxide.

[0010] In step (1), the total molar ratio of lithium in the lithium source to nickel, cobalt, and manganese metals in the precursor is 1:(1 to 1.1), for example:1:1, 1:1.02, 1:1.05, 1:1.08, or 1:1.1.

[0011] In one embodiment, the mass percentage of the nano-oxide in the finished single crystal high nickel cathode material is 0.05% to 0.3%, such as 0.05%, 0.08%, 0.1%, 0.2% or 0.3%.

[0012] In one embodiment, the mixing speed in step (1) is 500 to 3000 rpm, such as 500 rpm, 800 rpm, 1000 rpm, 2000 rpm, or 3000 rpm.

[0013] In one embodiment, the mixing time in step (1) is 10 to 30 minutes, such as 10 minutes, 12 minutes, 15 minutes, 20 minutes, 25 minutes, or 30 minutes.

[0014] In one embodiment, the flow rate of the oxygen in step (1) is 5-20 L / min, such as 5 L / min, 10 L / min, 12 L / min, 15 L / min, or 20 L / min.

[0015] In one embodiment, the temperature of the primary sintering treatment in step (1) is 800 to 950°C, for example, 800°C, 850°C, 900°C, or 950°C.

[0016] In one embodiment, the heating rate of the primary sintering treatment in step (1) is 2 to 5° C. / min, for example, 2° C. / min, 3° C. / min, 4° C. / min, or 5° C. / min.

[0017] In one embodiment, the time for the primary sintering treatment in step (1) is 5 to 15 hours, such as 5 hours, 8 hours, 10 hours, 12 hours, or 15 hours.

[0018] In one embodiment, after the primary sintering process in step (1), the primary sintered material is crushed, ground and sieved.

[0019] In one embodiment, the sieve has a pore size of 300 to 400 mesh, for example, 300 mesh, 320 mesh, 350 mesh, 380 mesh, or 400 mesh.

[0020] In one embodiment, the titanium source in step (2) comprises any one or a combination of at least two of titanium oxide, titanium hydroxide, or titanium sulfate.

[0021] In one embodiment, the cobalt source in step (2) comprises any one or a combination of at least two of tricobalt tetroxide, cobalt chloride, cobalt acetate, cobalt nitrate, cobalt hydroxide, or cobalt sulfate.

[0022] In one embodiment, the mass ratio of the primary sintering material, titanium source and cobalt source is 1:(0.001-0.006):(0.001-0.015), such as 1:0.001:0.001, 1:0.003:0.002, 1:0.005:0.01, 1:0.005:0.012 or 1:0.006:0.015.

[0023] In one embodiment, the mixing speed in step (2) is 800-2000 rpm, such as 800 rpm, 1000 rpm, 1200 rpm, 1500 rpm, or 2000 rpm.

[0024] In one embodiment, the mixing time in step (2) is 10 to 30 minutes, such as 10 minutes, 12 minutes, 15 minutes, 20 minutes, 25 minutes, or 30 minutes.

[0025] In one embodiment, the flow rate of the oxygen in step (2) is 5-20 L / min, such as 5 L / min, 10 L / min, 12 L / min, 15 L / min, or 20 L / min.

[0026] In one embodiment, the temperature of the secondary sintering treatment in step (2) is 500 to 850°C, for example, 500°C, 650°C, 700°C, or 950°C.

[0027] In one embodiment, the heating rate of the secondary sintering treatment in step (2) is 2 to 5°C / min, for example, 2°C / min, 3°C / min, 4°C / min, or 5°C / min.

[0028] In one embodiment, the time for the secondary sintering treatment in step (2) is 4 to 20 hours, such as 4 hours, 8 hours, 10 hours, 15 hours, or 20 hours.

[0029] In one embodiment, the single crystal high-nickel positive electrode material is crushed and sieved after the secondary sintering process in step (2).

[0030] In one embodiment, the sieve has a pore size of 300 to 400 mesh, for example, 300 mesh, 320 mesh, 350 mesh, 380 mesh, or 400 mesh.

[0031] In one embodiment, the present disclosure provides a single crystal high-nickel positive electrode material, the single crystal high-nickel positive electrode material being prepared by the above-mentioned method.

[0032] The present disclosure provides, in one embodiment, a cathode tab, the cathode tab including the single crystal high nickel cathode material described above.

[0033] In one embodiment, the specific surface area of ​​the monocrystalline high nickel positive electrode material is 0.5 to 0.8 m 2 / g, e.g., 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g or 0.8m 2 / g, etc.

[0034] In one embodiment, the pH of the monocrystalline high-nickel cathode material is ≦11.8, such as 10, 10.2, 10.8, 11, 11.5, or 11.8.

[0035] In one embodiment, the residual alkali of the single crystal high nickel positive electrode material is ≦3500 ppm, such as 3000 ppm, 3100 ppm, 3200 ppm, 3300 ppm, 3400 ppm, or 3500 ppm.

[0036] In one embodiment, the present disclosure provides a lithium ion battery, the lithium ion battery including the positive electrode tab described above.

[0037] The drawings are intended to provide a further understanding of the technical solutions of the present specification, constitute a part of the specification, and are used to explain the technical solutions of the present specification together with the examples of the present application, and are not intended to limit the technical solutions of the present specification. [Brief description of the drawings]

[0038] [Figure 1] FIG. 2 is an SEM view of a single crystal high nickel cathode material according to one embodiment of the present disclosure. [Diagram 2] 5 is a 50-week cycle curve at 3.0 to 4.3 V of a single crystal high-nickel positive electrode material according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0039] The present disclosure provides in one embodiment a method for preparing a single crystal high nickel positive electrode material, the method comprising: (1) mixing a precursor, a lithium source and a nano-oxide, and obtaining a primary sintered material by a primary sintering process under an oxygen-containing atmosphere; and step (2) mixing the primary sintered material obtained in step (1) with a titanium source and a cobalt source, and subjecting the primary sintered material to a secondary sintering process in an oxygen-containing atmosphere to obtain the single crystal high-nickel positive electrode material.

[0040] The present disclosure employs the doping of nano-oxide with precursor and lithium source to reduce the mixing of lithium nickel, stabilize the crystal structure, improve the conductivity of the electrode material, and further improve the safety and long-term cycle stability of the battery. The present disclosure employs the Ti / Co co-coating method to significantly reduce the residual alkali content of the prepared single crystal high nickel positive electrode material while maintaining high capacity and rate performance, thereby reducing the process flow and reducing costs.

[0041] In one embodiment, the precursor in step (1) is Ni x Co y Mn z (OH) 2 wherein x≧0.8, such as 0.8, 0.82, 0.85 or 0.88; 0.2≧y≧0, such as 0, 0.05, 0.1, 0.15 or 0.2; 0.2≧z≧0, such as 0, 0.05, 0.1, 0.15 or 0.2; and x+y+z=1.

[0042] In one embodiment, the lithium source in step (1) comprises lithium hydroxide and / or lithium carbonate.

[0043] In one embodiment, the nano-oxide in step (1) comprises any one or a combination of at least two of zirconium oxide, titanium oxide, tungsten oxide, molybdenum oxide, alumina, or yttrium oxide.

[0044] In step (1), the total molar ratio of lithium in the lithium source to nickel, cobalt and manganese metals in the precursor is 1:(1 to 1.1), for example:1:1, 1:1.02, 1:1.05, 1:1.08 or 1:1.1.

[0045] In one embodiment, the mass percentage of the nano-oxide in the finished single crystal high nickel cathode material is 0.05% to 0.3%, such as 0.05%, 0.08%, 0.1%, 0.2% or 0.3%.

[0046] In one embodiment, the mixing speed in step (1) is 500 to 3000 rpm, such as 500 rpm, 800 rpm, 1000 rpm, 2000 rpm, or 3000 rpm.

[0047] In one embodiment, the mixing time in step (1) is 10 to 30 minutes, such as 10 minutes, 12 minutes, 15 minutes, 20 minutes, 25 minutes, or 30 minutes.

[0048] In one embodiment, the flow rate of the oxygen in step (1) is 5-20 L / min, such as 5 L / min, 10 L / min, 12 L / min, 15 L / min, or 20 L / min.

[0049] In one embodiment, the temperature of the primary sintering treatment in step (1) is 800 to 950°C, for example, 800°C, 850°C, 900°C, or 950°C.

[0050] The sintering temperature in step (1) of the present disclosure affects the residual alkali content of the prepared single crystal high nickel positive electrode material, and by controlling the sintering temperature to 800-950°C, a single crystal high nickel positive electrode material with a low residual alkali content can be prepared. When the temperature is below 800°C, on the one hand, the residual alkali content of the material is improved, and on the other hand, the primary particles are small, which affects the cycle stability of the material; when it exceeds 950°C, the primary particles of the material are greatly increased, and the capacity is correspondingly greatly reduced.

[0051] In one embodiment, the heating rate of the primary sintering treatment in step (1) is 2 to 5° C. / min, for example, 2° C. / min, 3° C. / min, 4° C. / min, or 5° C. / min.

[0052] In one embodiment, the time for the primary sintering treatment in step (1) is 5 to 15 hours, such as 5 hours, 8 hours, 10 hours, 12 hours, or 15 hours.

[0053] In one embodiment, after the primary sintering process in step (1), the primary sintered material is crushed, ground and sieved.

[0054] In one embodiment, the sieve has a pore size of 300 to 400 mesh, for example, 300 mesh, 320 mesh, 350 mesh, 380 mesh, or 400 mesh.

[0055] In one embodiment, the titanium source in step (2) comprises any one or a combination of at least two of titanium oxide, titanium hydroxide, or titanium sulfate.

[0056] In one embodiment, the cobalt source in step (2) comprises any one or a combination of at least two of tricobalt tetroxide, cobalt chloride, cobalt acetate, cobalt nitrate, cobalt hydroxide, or cobalt sulfate.

[0057] In one embodiment, the mass ratio of the primary sintering material, titanium source and cobalt source is 1:(0.001-0.006):(0.001-0.015), such as 1:0.001:0.001, 1:0.003:0.002, 1:0.005:0.01, 1:0.005:0.012 or 1:0.006:0.015.

[0058] The mass ratio of the primary sintering material, titanium source, and cobalt source described in the present disclosure affects the residual alkali amount of the prepared single crystal high-nickel positive electrode material, and by controlling the mass ratio of the primary sintering material, titanium source, and cobalt source to 1:(0.001-0.006):(0.001-0.015), a single crystal high-nickel positive electrode material with a low residual alkali amount can be prepared.

[0059] In one embodiment, the mixing speed in step (2) is 800-2000 rpm, such as 800 rpm, 1000 rpm, 1200 rpm, 1500 rpm, or 2000 rpm.

[0060] In one embodiment, the mixing time in step (2) is 10 to 30 minutes, such as 10 minutes, 12 minutes, 15 minutes, 20 minutes, 25 minutes, or 30 minutes.

[0061] In one embodiment, the flow rate of the oxygen in step (2) is 5-20 L / min, such as 5 L / min, 10 L / min, 12 L / min, 15 L / min, or 20 L / min.

[0062] In one embodiment, the temperature of the secondary sintering treatment in step (2) is 500 to 850°C, for example, 500°C, 650°C, 700°C, or 950°C.

[0063] The sintering temperature in step (2) of the present disclosure affects the residual alkali content of the prepared single crystal high nickel positive electrode material. By controlling the sintering temperature to 500-850°C, a single crystal high nickel positive electrode material with a low residual alkali content can be prepared. If the temperature is less than 500°C, the bond between the coating layer and the primary sintering substrate will not be strong enough, and the coating layer will partially fall off during the cycle process, the contact area between the electrolyte and the positive electrode material will increase, side reactions will increase, the battery will swell, and the cycle performance will deteriorate. If the temperature exceeds 850°C, hard agglomeration and blocking of the primary particles will occur, making it difficult to directly sieve, and the crushing process needs to be increased to open the agglomeration, and at the same time, the size of the primary particles will be increased, which will affect the material capacity.

[0064] In one embodiment, the heating rate of the secondary sintering treatment in step (2) is 2 to 5° C. / min, for example, 2° C. / min, 3° C. / min, 4° C. / min, or 5° C. / min.

[0065] In one embodiment, the time for the secondary sintering treatment in step (2) is 4 to 20 hours, such as 4 hours, 8 hours, 10 hours, 15 hours, or 20 hours.

[0066] In one embodiment, the single crystal high-nickel positive electrode material is crushed and sieved after the secondary sintering process in step (2).

[0067] In one embodiment, the sieve has a pore size of 300 to 400 mesh, for example, 300 mesh, 320 mesh, 350 mesh, 380 mesh, or 400 mesh.

[0068] In one embodiment, the present disclosure provides a single crystal high-nickel positive electrode material, the single crystal high-nickel positive electrode material being prepared by the above-mentioned method.

[0069] The present disclosure provides, in one embodiment, a cathode tab, the cathode tab comprising the single crystal high nickel cathode material described above.

[0070] In one embodiment, the specific surface area of ​​the monocrystalline high nickel positive electrode material is 0.5 to 0.8 m 2 / g, e.g., 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g or 0.8m 2 / g, etc.

[0071] In one embodiment, the pH of the monocrystalline high-nickel cathode material is ≦11.8, such as 10, 10.2, 10.8, 11, 11.5, or 11.8.

[0072] In one embodiment, the residual alkali of the single crystal high nickel positive electrode material is ≦3500 ppm, such as 3000 ppm, 3100 ppm, 3200 ppm, 3300 ppm, 3400 ppm, or 3500 ppm.

[0073] In one embodiment, the present disclosure provides a lithium ion battery, the lithium ion battery including the positive electrode tab described above.

[0074] Example 1 This example provides a single crystal high nickel positive electrode material, and specifically includes the following steps: (1) Ni 0.83 Co 0.11 Mn 0.06 (OH) 2and lithium hydroxide are weighed with lithium / metal=1.03:1, put into a high-speed mixer, add 0.1% nano zirconium oxide, mix at 1000 rpm for 20 minutes, heat to 850℃ with 10L / min oxygen flow rate and 3℃ / min heating rate, sinter for 10 hours, cool to room temperature, crush, and then sieve through a 300 mesh sieve to obtain the primary sintered material. (2) The primary sintered material obtained in step (1) was mixed with titanium oxide and tricobalt tetroxide in a mass ratio of 1:0.003:0.008, heated to 800°C at an oxygen flow rate of 10 L / min and a heating rate of 3°C / min, sintered for 15 hours, cooled to room temperature, crushed, and then sieved through a 300 mesh sieve to obtain the single crystal high-nickel positive electrode material.

[0075] The SEM image of the single crystal high-nickel positive electrode material is shown in FIG. 1. From FIG. 1, it can be seen that the coating layer on the surface of the single crystal particle of the single crystal high-nickel positive electrode material prepared by the method disclosed herein is uniform.

[0076] The cycle curve of the single crystal high nickel positive electrode material at 3.0-4.3 V for 50 weeks is shown in FIG.

[0077] Example 2 This example provides a single crystal high nickel positive electrode material, and specifically includes the following steps: (1) Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 and lithium hydroxide are weighed in a lithium / metal ratio of 1:1, and then put into a high-speed mixer. Then, 0.15% nano-tungsten oxide is added, and mixed at 1500 rpm for 20 minutes. The oxygen flow rate is 12 L / min, and the temperature is increased to 900°C at a heating rate of 4°C / min. Sintering is performed for 8 hours. The mixture is cooled to room temperature and crushed, and then sieved through a 400 mesh sieve to obtain the primary sintered material. (2) The primary sintered material obtained in step (1) was mixed with titanium hydroxide and cobalt chloride in a mass ratio of 1:0.005:0.012, heated to 750°C at an oxygen flow rate of 12 L / min and a heating rate of 4°C / min, sintered for 12 hours, cooled to room temperature, crushed, and then sieved through a 400 mesh sieve to obtain the single crystal high nickel positive electrode material.

[0078] Example 3 The difference between this example and Example 1 is that the sintering temperature in step (1) is 800°C.

[0079] Example 4 The difference between this example and Example 1 is that the sintering temperature in step (1) is 950°C.

[0080] Example 5 The difference between this embodiment and embodiment 1 is that the sintering temperature in step (2) is 500°C.

[0081] Example 6 The difference between this embodiment and embodiment 1 is that the sintering temperature in step (2) is 850°C.

[0082] Example 7 The present embodiment is different from Example 1 in that the mass ratio of the primary sintering material to titanium oxide in step (2) is 1:0.001.

[0083] Example 8 The present embodiment is different from Example 1 in that the mass ratio of the primary sintering material to titanium oxide in step (2) is 1:0.006.

[0084] Example 9 The present embodiment is different from Example 1 in that the mass ratio of the primary sintering material to tricobalt tetroxide in step (2) is 1:0.001.

[0085] Example 10 The present embodiment is different from Example 1 in that the mass ratio of the primary sintering material to tricobalt tetroxide in step (2) is 1:0.015.

[0086] Comparative Example 1 The difference between this comparative example and Example 1 is that titanium oxide was not added.

[0087] Comparative Example 2 The difference between this comparative example and Example 1 is that tricobalt tetroxide was not added.

[0088] Comparative Example 3 The difference between this comparative example and Example 1 is that titanium oxide and tricobalt tetroxide were not added.

[0089] The single crystal high-nickel positive electrode materials prepared in Examples 1 to 10 and Comparative Examples 1 to 3 were evaluated. 1. Residual alkali test step (1) Sample treatment: Weigh out 10g of sample, put it into a 250mL dry beaker, add 100mL of pure water, add a magnetic stirrer to the beaker and cover it with plastic wrap, stir with a magnetic stirrer for 30 minutes, leave it for 2 minutes after stirring is completed, take a clean funnel and place it in a clean conical flask, fold the circular filter paper in half and put it into the funnel to filter, and after filtering, cover the conical flask with a rubber cap; (2) Select the test method you need, click to load, (3) Transfer 50 mL of the solution to a titration cup (adjustable according to circumstances) using a pipette, enter the sample mass into the potential titrator software, add 100 mL of ultrapure water to dilute, press the start button and measure. (4) When two obvious titration inflection points appear during the measurement process, it is considered that the titration end point has been reached, and the test is terminated by pressing the END key. The two inflection points are V 1 and V 2 and (5) Calculated.

[0090] Calculation of lithium carbonate content X 2=c*(V 2 -V 1 )*73.89*2 / 1000 / m*100% V 1 - the volume of standard solution used to titrate the sample being measured to the first obvious inflection point, in milliliters (mL); V 2 - the volume of standard solution used to titrate the sample being measured to the second obvious inflection point, in milliliters (mL); c-Hydrogen acid standard concentration, c(HCl) = 0.05 mol / L, according to GB / T601. Calculating lithium hydroxide content X 3 =c*(2V 1 -V 2 )*23.95*2 / 1000 / m*100% where 23.95 g / mol is the molar mass of lithium hydroxide, 73.98 g / mol is the molar mass of lithium carbonate. m is the sample mass in g, and the test results are shown in Table 1.

[0091] [Table 1]

[0092] From Table 1, comparing Example 1 with Examples 3-4, it can be seen that the sintering temperature in step (1) affects the residual alkali content of the prepared single crystal high nickel positive electrode material, and by controlling the sintering temperature to 800-950°C, a single crystal high nickel positive electrode material with a low residual alkali content can be prepared; when the temperature is less than 800°C, on the one hand, the residual alkali content of the material is improved, and on the other hand, the primary particles are small, which affects the cycle stability of the material; when the temperature exceeds 950°C, the primary particles of the material are greatly increased, and the capacity is correspondingly greatly reduced.

[0093] Comparing Example 1 and Examples 5-6, it is found that the sintering temperature in step (2) affects the residual alkali content of the prepared single crystal high nickel positive electrode material. By controlling the sintering temperature to 500-850°C, a single crystal high nickel positive electrode material with a low residual alkali content can be prepared. If the temperature is less than 500°C, the bond between the coating layer and the primary sintering substrate is not strong enough, and the coating layer is partially dropped off during the cycle process, the contact area between the electrolyte and the positive electrode material increases, side reactions increase, the battery swells, and the cycle performance deteriorates. If the temperature exceeds 850°C, hard agglomeration and blocking of the primary particles occurs, making it difficult to directly sieve, and the crushing process needs to be increased to open the agglomeration. In addition, the size of the primary particles increases, which affects the material capacity.

[0094] Comparing Example 1 with Examples 7 to 10, it was found that the mass ratio of the primary sintering material, titanium source, and cobalt source in step (2) affects the residual alkali amount of the prepared single crystal high-nickel positive electrode material, and by controlling the mass ratio of the primary sintering material, titanium source, and cobalt source to 1:(0.001-0.006):(0.001-0.015), a single crystal high-nickel positive electrode material with a low residual alkali amount can be prepared.

[0095] For the final single crystal high nickel positive electrode material obtained in Examples 1-10 and Comparative Examples 1-3, a button half cell charge-discharge test is carried out, specifically, the single crystal high nickel positive electrode material: polyvinylidene fluoride (PVDF): superconducting carbon black (SP) conductive agent is mixed in a ratio of 92:4:4, N-methylpyrrolidone (NMP) is added to adjust the slurry solid content to 50%, and then the slurry is uniformly applied to aluminum foil and baked at 100 ° C for 12 hours to produce the entire tab, and then the entire tab is cut into three pieces and roll pressed, and the three roll pressed tabs are cut into circular tabs with a diameter of 12 mm, and the battery is assembled in a glove box, and the negative electrode is a lithium piece. The test results are shown in Table 2.

[0096] [Table 2]

[0097] From Table 2, comparing Examples 1 to 10, it can be seen that the 0.1C charge capacity of the battery manufactured using the method described in the present disclosure can reach 226.3mAh / g or more, the 0.1C discharge capacity can reach 205mAh / g or more, the 1C discharge capacity can reach 187.2mAh / g or more, the initial coulombic efficiency can reach 90.5% or more, and the 50-week cycle retention rate can reach 95.5% or more.

[0098] Comparing Example 1 and Examples 3-4, it is found that the sintering temperature in step (1) affects the performance of the prepared single crystal high nickel positive electrode material, and by controlling the sintering temperature to 800-950°C, a single crystal high nickel positive electrode material with good performance can be prepared. The primary sintering temperature affects the size of the single crystal primary particles, and when the temperature is low, the primary particles are small, the capacity is high, but the cycle performance is poor; when the temperature is high, the primary particles are large, the capacity is low, but the cycle performance is good. Based on the above, a material with good performance in all aspects was obtained by selecting the primary sintering temperature range of 800-950°C. When the temperature is less than 800°C, the growth of the single crystal primary particles is small, which affects the cycle performance of the material; when the temperature is more than 950°C, the growth of the single crystal primary particles is large, the cycle performance is better, but the capacity is greatly reduced.

[0099] Comparing Example 1 and Examples 5-6, it is found that the sintering temperature in step (2) affects the performance of the prepared single crystal high nickel positive electrode material. By controlling the sintering temperature to 500-850°C, a single crystal high nickel positive electrode material with good performance can be prepared. If the secondary sintering temperature is less than 500°C, the bond between the coating layer and the primary sintering substrate is not strong enough, and the coating layer is partially dropped off during the cycle process, the contact area between the electrolyte and the positive electrode material increases, side reactions increase, the battery swells, and the cycle performance deteriorates. If the secondary sintering temperature exceeds 850°C, the primary particles will harden and aggregate, blocking will occur, making it difficult to directly sieve, and the crushing process needs to be increased to open the aggregate. At the same time, the size of the primary particles will increase, which will affect the material capacity.

[0100] Comparing Example 1 with Examples 7 to 10, it was found that the mass ratio of the primary sintering material, titanium source, and cobalt source in step (2) affects the performance of the prepared single crystal high-nickel positive electrode material, and by controlling the mass ratio of the primary sintering material, titanium source, and cobalt source to 1:(0.001-0.006):(0.001-0.015), it is possible to prepare a single crystal high-nickel positive electrode material with good performance.

Claims

1. 1. A method for preparing a single crystal high nickel positive electrode material, comprising: (1) mixing a precursor, a lithium source and a nano-oxide, and obtaining a primary sintered material through a primary sintering process under an oxygen-containing atmosphere; and step (2) mixing the primary sintered material obtained in step (1) with a titanium source and a cobalt source, and obtaining the single crystal high-nickel positive electrode material through a secondary sintering process in an oxygen-containing atmosphere; In step (2), the mass ratio of the primary sintering material, the titanium source, and the cobalt source is 1:(0.001-0.006):(0.001-0.015); The preparation method, characterized in that the temperature of the primary sintering treatment in step (1) is 800 to 950 ° C, and the temperature of the secondary sintering treatment in step (2) is 500 to 850 ° C.

2. The precursor in step (1) is Ni x Co y Mn z (OH) 2 Includes 、 2. The method according to claim 1, wherein x≧0.8, 0.2≧y≧0, 0.2≧z≧0, and x+y+z=1.

3. 2. The method according to claim 1, wherein the nano-oxide in step (1) comprises any one or a combination of at least two of zirconium oxide, titanium oxide, tungsten oxide, molybdenum oxide, alumina, or yttrium oxide.

4. 2. The method according to claim 1, wherein the mass percentage of the nano-oxide in the finished single crystal high-nickel cathode material is 0.05%-0.3%.

5. The preparation method according to claim 1, characterized in that the time of the primary sintering treatment in step (1) is 5-15h.

6. The preparation method according to claim 1, characterized in that the time of the secondary sintering treatment in step (2) is 4 to 20 h.

Citation Information

Patent Citations

  • Surface coating type ternary positive electrode material and preparation method thereof

    CN106941162A

  • High-nickel ternary positive electrode material with monocrystal morphology and preparation method of high-nickel ternary positive electrode material

    CN108023078A

  • Preparation method of high-voltage lithium cobalt oxide cathode material

    CN109326781A

  • High-nickel single-crystal ternary cathode material with low surface residual alkali content and preparation method thereof

    CN110436531A

  • Method for preparing high-nickel long-cycle single-crystal lithium ion battery positive-pole material

    CN110451585A